Use of constructed wetlands for the treatment of water from an experimental channel at Xochimilco, Mexico - Martínez-Cruz, Patricia; Hernández-Martínez, Armando; Soto-Castor, Ruth; Esquivel Herrera, Alfonso; Rangel Levario, Jesús (HIDROBIOLÓGICA, 2017)
Two constructed wetlands were designed and their performance in the treatment of water from Cuemanco, in an experimental channel at Xochimilco, Mexico was assessed. One of them employed emergent macrophytes (Scirpus americanus) and the other one used floating macrophytes (the duckweed Lemna gibba). The system was stabilized for five months. Water quality was improved after 220 days of treatment, as organic matter (assessed as DQO) was removed from 43.38% to 58.52% by employing L. gibba and S. americanus, respectively. Nutrient removal significatively (P < 0.05) differed between the two treatments and the control, as 86.35% and 80.33% of ammonia, 89.47% and 90.23% of nitrite, and 38.44% and 50.20% of reactive phosphorus were removed by S. americanus and L. gibba, respectively. On the other hand, water pH changed from alkaline values to neutrality after the treatment, an important issue as this water is employed for cultured land irrigation.